Optimization of formulation for a snack food using coconut residue flour - Basaca, Myla Castillo; Galvez, Flor Crisanta F. (1995)
The formulation for coconut residue flour (CRF) chips acceptable to consumers was optimized in two phases using response surface methodology (RSM). Phase I involved the determination of the effect of amount of CRF (0,15 and 30% substitution of the wheat flour) and water (45, 50, 55%) on consumer acceptability of the product. In phase II, the influence of the fat content of CRF (23, 28 and 33%) and increased amounts of CRF (20, 35 and 50% substitution of wheat flour) was investigated. twenty - four consumer panelists evaluated all samples for acceptability of appearance, flavor and texture, and overall acceptability using 9 - point hedonic scales. A consumer acceptance rating of 5.0 or greater was used as the lowest limit for optimization of each attribute. Results indicated that texture and flavor were the limiting factors for the consumer acceptability of the product. Water added at the levels used in this study was found not to have any significant effect on the acceptance scores. A substitution level of up to 50% of the wheat flour with CRF and a fat content of CRF of up to 28% using enough water to form a dough will give CRF chips that have acceptable appearance, flavor, texture and overall acceptability.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Coconut flour; Snack foods